Ayurvedic Management of Diabetes Mellitus (DM) and Diabetic Neuropathy: A Case Study - Vishal Mori; Manish Patel; S N Gupta; Pankaj Chhayani (International Journal of Ayurveda and Pharma Research, 2023)
Diabetes is a burning problem of modern world and is associated with multiple complications. All oral hyoglycemic drugs and insulin used in modern medicine only help to lower blood sugar of body. The biological medicines are only available treatments which have limited effect and carrying many serious adverse effects. Purpose: The conventional medicine has its own limitation in this disease condition, it only help to lower blood sugar level of body and in a long run it has shown its side effects. They neither able to correct the pathology nor helpful to protect vital organs of the body and to prevent further complications. Ayurvedic treatment approaches are helpful in this disease. With the changing demand and awareness among these days, the role of Ayurveda is an emerging reality. Brief case history: A 49-year-old, married, Hindu male patient visited PD Patel Ayurvedic Hospital on 9th November 2021. He had been diagnosed with type 2 diabetes above 11 years and received medication for this. He was taking Tab. Metformine since last 11 years. He had chief complains of Madhuryamasyata, Karapadadaha, Pipasadhikya, Mootraadhikya since last 11 years, and other associated complains were Kshudha Vriddhi, Atichinta, and Nidravriddhi since last 4 months. He had gradually increased body weight in last year 2 years. He had been admitted and treated with Virechna karma and Basti chikitsa and oral Ayurvedic medicines for one month. After one month of treatment, he is continuing oral medicines only and he regularly comes for following up in OPD. Now on the second follow up patient had much improvement in above symptoms. His blood sugar level and weight were also reduced significantly. Result: He got an excellent result with complete relief from all symptoms as well as marked reduction in objective criteria (lab investigation) within 1 month.